Readiness Evaluation of the Multimedia Technology Teachers in Implementing Curriculum 2011 in Timor-Leste - Savio, Leovelgilda Fernandes; Samsudi, Samsudi; Prihatin, Titi (Universitas Negeri Semarang, 2020)
The implementation of the Timor-Leste curriculum 2011 for the multimedia technology subject at Public High School in Baucau sub-district needs to be evaluated for maintaining the consistency of the curriculum objective achievements. This research aims to know the teachers’ readiness in implementing the Timor-Leste curriculum 2011. The aspects considered are official language competence, academic qualification, pedagogical competence, and professional competence. This research is a survey analysis using 7 respondents of multimedia technology teachers. The result of the research shows that the teachers at Public High School 01 and 02 in Baucau Sub-district are in the